The role of innovation and technology in achieving sustainability in China’s private enterprises - Zhang, Binwei; Wang, Zhijian; Miao, Shaowei; Zhang, Zijie (Edelweiss Applied Science and Technology, 2025)
This study explores the pivotal role of innovation and technology in fostering sustainability within China’s private enterprises. Given their substantial contribution to the national economy, these enterprises are at the forefront of embracing digital transformation as a strategy for long-term growth. However, despite advancements in technology, challenges such as leadership gaps, insufficient performance evaluation, and resource constraints hinder their full potential. The research focuses on how emerging technologies—particularly digital tools such as artificial intelligence, big data, and information systems—can drive innovation while aligning with sustainability goals. The findings highlight that digital transformation not only enhances operational efficiency but also fosters innovative practices that contribute to sustainability. Additionally, government innovation policies and financial incentives are critical in facilitating this transition. The paper concludes by offering strategic recommendations for private enterprises to integrate technology and innovation to overcome existing challenges, thereby enhancing their competitiveness and promoting sustainable business practices.